Pump station control system under climate risks and temperature extremes - Shuxrat B. Umarov; Saidamirxon H. Oripov (PROBLEMS OF ENERGY AND SOURCES SAVING, 2026)
Relevance: in extremely harsh operating conditions of pump installations in open areas, especially in the mining and water management industries, the problem of equipment freezing at low temperatures becomes particularly acute. This leads to damage to pump units, disruptions in technological processes, and additional repair costs. Therefore, the development and implementation of simple and reliable automatic anti-freeze protection systems is of great relevance. Aim: development and experimental validation of the performance of an automatic anti-freeze protection system for a pump unit based on a microcontroller and temperature sensor. Methods: the study used digital signal processing methods, microcontroller-based control, simulation modeling of the decision-making algorithm, and laboratory testing on a model installation. Results: a system was developed that implements an algorithm for assessing the condition of the main pump based on current and ambient temperature. When a freezing hazard is detected, an auxiliary pump is automatically activated to maintain minimal water circulation. The functionality of the circuit, temperature response accuracy, and reliability of all components during extended operation have been experimentally confirmed.